DESIGN THINKING APPROACHES IN DEVELOPMENT OF INDONESIA HIGHER EDUCATION STARTUP - Didit - Herawan (JOBS (Jurnal Of Business Studies), 2019)
The Design Thinking approach as a method of problem solving and product innovation is well known in business, management and entrepreneurship. However, various design thinking models created by individual researcher and corporations often confuse users about which model to use. This research was conducted with the aim of observing the suitability of five selected design thinking models to support the development of startups in a business incubator. The research applies qualitative descriptive method using a case study of PT. Jiwa Gelora Juara (PT-JGJ) startup development at the Bakrie University’s UBpreneur business incubator. It observes the design thinking process in the pre-incubation, incubation and post incubation stages. The research findings show that each design thinking model has its own strengths and weaknesses in a certain situation, but most of the models are more suitable implemented in the new product/process development phase. To support the startup’s growth stage, other management tools are needed.